Moisture-curing polyurethane hot melt resin composition, cured product, and laminate
Patent Information
- Application Number
- CN202111494652.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-01-26
- Filing Date
- 2021-12-07
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2041-12-07
AI Technical Summary
[0023]本发明的湿气固化型聚氨酯热熔树脂组合物能够在湿气固化后也确保透明性并且抑制发泡,进而发挥向PET基材的粘接性。
Smart Images

Figure BDA0003397378920000061 
Figure BDA0003397378920000131
Abstract
Description
Technical Field
[0001] This invention relates to moisture-curing polyurethane hot melt resin compositions, cured products, and laminates. Background Technology
[0002] Hot melt adhesives, due to their high initial adhesion and final strength, are widely used in various building materials applications, including decorative panels, automotive interior materials, and clothing. As reactive hot melt adhesives, besides moisture-curing polyurethane hot melt adhesives that achieve final strength through moisture curing of the isocyanate groups in their main component, urethane prepolymers, olefin-based hot melt adhesives and polyester-based hot melt adhesives are also known. In recent years, there has been an increasing demand for high-end building materials obtained by attaching highly transparent materials such as polyethylene terephthalate (PET) films to substrates.
[0003] Examples of highly transparent hot melt adhesives include, for instance, hot melt adhesives comprising ethylene-propylene copolymers, hydrogenated rosin-based tackifying resins, other hydrogenated tackifying resins, and acid-modified olefins (see Patent Document 1); crystalline polyester resins formed from polycarboxylic acid components and polyol components, wherein terephthalic acid is included as a polycarboxylic acid component, and ethylene glycol, 1,4-butanediol, polyalkylene glycol, and diethylene glycol are included as polyol components (see Patent Document 2); hot melt adhesives comprising ethylene-propylene copolymers, hydrogenated tackifying resins, and waxes with melting points of 120–160°C (see Patent Document 3); and polyester resins comprising polycarboxylic acid components and polyol components as copolymer components, containing aromatic dicarboxylic acids with 8–14 carbon atoms and aliphatic dicarboxylic acids with 6 or more carbon atoms as polycarboxylic acid components, and further containing aliphatic carboxylic acid metal salts with 6 or more carbon atoms (see Patent Document 4).
[0004] Existing technical documents
[0005] Patent documents
[0006] [Patent Document 1] Japanese Patent Application Publication No. 2020-2283
[0007] [Patent Document 2] Japanese Patent Application Publication No. 2019-127581
[0008] [Patent Document 3] Japanese Patent Application Publication No. 2018-154694
[0009] [Patent Document 4] Japanese Patent Application Publication No. 2015-108113 Summary of the Invention
[0010] The problem that the invention aims to solve
[0011] However, when using reactive hot melt adhesives (RHM) for such applications, high transparency of the resin itself is required, and consequently, foam suppression during moisture curing of the RHM is also necessary. According to the research of the inventors, using crystalline components as raw materials is effective in suppressing foaming, but the resulting cured product suffers from problems such as cloudiness and reduced transparency due to crystallization of the crystalline components.
[0012] The present invention was made in view of the above circumstances, and its objective is to provide a moisture-curing polyurethane hot melt adhesive that can ensure transparency and suppress foaming even after moisture curing, thereby achieving adhesion to PET substrates.
[0013] Methods for solving problems
[0014] Through in-depth research, the inventors conceived of combining alicyclic polyester polyols, crystalline components, and liquid polyester. While alicyclic polyester polyols are generally not expected to have good adhesion to PET substrates, it was discovered that by combining them in a specific ratio, transparency could be maintained and foaming suppressed, thereby ensuring adhesion to the PET substrate, thus completing this invention.
[0015] That is, the present invention includes the following inventions.
[0016] [1] A moisture-curing polyurethane hot melt resin composition comprising a polyurethane resin having an isocyanate group, wherein the polyurethane resin is a reaction product of a polyol (A) and a polyisocyanate (B), wherein the polyol (A) comprises an alicyclic polyester polyol (a1), a long-chain aliphatic polyester polyol (a2), and a liquid polyester polyol (a3), wherein the alicyclic polyester polyol (a1) contains 20% by mass or more in the polyol (A), the long-chain aliphatic polyester polyol (a2) contains 15% by mass or more in the polyol (A), and the liquid polyester polyol (a3) contains 15% by mass or more in the polyol (A).
[0017] [2] The moisture-curing polyurethane hot melt resin composition according to [1] has a haze value of less than 20 as determined by the following method.
[0018] [Methods for measuring haze]
[0019] A moisture-curing polyurethane hot-melt resin composition was melted at 120°C for 1 hour and then coated onto a release layer to achieve a thickness of 0.1 mm. The resulting coating layer was then maintained at 23°C and 50% humidity for 96 hours to obtain a cured product. The haze value of the cured product was measured according to JIS K 7136.
[0020] [3] A cured product, which is a cured product of the moisture-curing polyurethane hot melt resin composition described in [1] or [2].
[0021] [4] A laminate having the cured material described in [3].
[0022] Invention Effects
[0023] The moisture-curing polyurethane hot melt resin composition of the present invention can ensure transparency and suppress foaming even after moisture curing, thereby achieving adhesion to PET substrates. Detailed Implementation
[0024] The moisture-curing polyurethane hot melt resin composition of the present invention comprises a polyurethane resin having isocyanate groups.
[0025] The polyurethane resin mentioned above is a reaction product of polyol (A) and polyisocyanate (B).
[0026] The aforementioned polyols (A) include alicyclic polyester polyols (a1), long-chain aliphatic polyester polyols (a2), and liquid polyester polyols (a3).
[0027] The aforementioned alicyclic polyester polyol (a1) is a polyester polyol containing an alicyclic structure in its molecule. By including an alicyclic polyester polyol (a1), transparency can be improved and foaming can be suppressed.
[0028] The aforementioned alicyclic polyester polyol (a1) is preferably, for example, the reaction product of a polyacid containing an alicyclic structure (hereinafter referred to as "polyacid containing an alicyclic structure") and a diol.
[0029] Regarding the aforementioned polyacids containing alicyclic structures, the presence of an alicyclic structure is sufficient. Examples include 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 1,2-cyclopropanedicarboxylic acid, 1,2-cyclobutanedicarboxylic acid, 1,3-cyclobutanedicarboxylic acid, 1,2-cyclopentanedicarboxylic acid, 1,3-cyclopentanedicarboxylic acid, 1,2-cycloheptanedicarboxylic acid, 1,3-cycloheptanedicarboxylic acid, 1,4-cycloheptanedicarboxylic acid, 1,2-cyclooctanedicarboxylic acid, 1,3-cyclooctanedicarboxylic acid, 1,4-cyclooctanedicarboxylic acid, 1,5-cyclooctanedicarboxylic acid, 1,2-cyclononanedicarboxylic acid, 1,3-cyclononanedicarboxylic acid, and 1,4-cyclononanedicarboxylic acid. Dicarboxylic acid, 1,5-cyclononanedicarboxylic acid, 1,2-cyclodecanedicarboxylic acid, 1,3-cyclodecanedicarboxylic acid, 1,4-cyclodecanedicarboxylic acid, 1,5-cyclodecanedicarboxylic acid, 1,6-cyclodecanedicarboxylic acid, 1,2,3-cyclopropanetricarboxylic acid, 1,2,3-cyclobutanetricarboxylic acid, 1,2,3-cyclopentanetricarboxylic acid, 1,2,3-cycloheptanetricarboxylic acid, 1,2,3-cyclohexanetricarboxylic acid, dicyclohexyl-4,4'-dicarboxylic acid and dimer acids, 1,2-cyclohexanediacetic acid, 1,3-cyclohexanediacetic acid, 1,4-cyclohexanediacetic acid, and their anhydrides; anhydrides of hydrogenated phthalic acid, etc., which may be used alone or in combination with two or more. Among them, dicarboxylic acids or their derivatives having a cyclohexane ring are preferred, and 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, and hydrogenated phthalic anhydride are more preferred.
[0030] The diols mentioned above are not particularly limited, and examples include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 2,2-dimethyl-1,3-propanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 1,8-octanediol, diethylene glycol, triethylene glycol, dipropylene glycol, tripropylene glycol, etc. (aliphatic diols); cyclopentane-1,2-diol, cyclohexane-1,2-diol, cyclohexane-1,3-diol, cyclohexane-1,4-diol, cyclooctane-1,4-diol, 2,5-norbornanediol, etc. (alicyclocyclic diols); neopentyl hydroxypentanoate, 2-methylpropanediol, 2-methyl-1,4-butanediol, neopentyl glycol, 2,2-di-propanediol, etc. Diols containing side chains, such as methyl-1,4-butanediol, 2,3-dimethyl-1,4-butanediol, 2-methyl-1,5-pentanediol, 3-methyl-1,5-pentanediol, 2,3-dimethyl-1,5-pentanediol, 3-ethyl-1,5-pentanediol, 2-methyl-1,6-hexanediol, 3-methyl-1,6-hexanediol, 2,3,4-trimethyl-1,5-pentanediol, 3,3-dimethyl-1,6-hexanediol, 3,3-diethyl-1,5-pentanediol, and 3,3-diethyl-1,6-hexanediol; aromatic diols, such as terephthalic acid, 4,4'-methylenediphenol, 4,4'-dihydroxybiphenyl, and 2,5-naphthalenediol, can be used alone or in combination of two or more.
[0031] Among them, from the viewpoint of appropriate opening time at low temperature and ease of obtaining raw materials, diols containing side chains are preferred, and neopentyl glycol, neopentyl glycol hydroxypentyl acid, and 2-methylpropanediol are more preferred.
[0032] The aforementioned alicyclic polyester polyol (a1) is obtained by polycondensation reaction of the aforementioned polyacid containing an alicyclic structure and a diol using conventionally known methods. For example, the polycondensation reaction can be carried out by adding the aforementioned polyacid containing an alicyclic structure and a diol to a reaction vessel, adding a high-boiling-point solvent such as xylene, an esterification catalyst, and a polymerization inhibitor as needed, to induce dehydration condensation, thereby conducting an esterification reaction. The reaction temperature of the polycondensation reaction is 140–240°C, more preferably 170–230°C, and the reaction time is 5–20 hours, more preferably 7–17 hours.
[0033] Examples of esterification catalysts include metal oxides such as tin oxide, antimony oxide, titanium oxide, and vanadium oxide; Brønsted acids such as p-toluenesulfonic acid, sulfuric acid, and phosphoric acid; Lewis acids such as boron trifluoride complexes, titanium tetrachloride, and tin tetrachloride; and organometallic compounds such as calcium acetate, zinc acetate, manganese acetate, zinc stearate, alkyltin oxide, and titanium alkoxides. These can be used alone or in combination with two or more.
[0034] The amount of the esterification catalyst used is preferably 0.001 to 0.1% by mass, more preferably 0.005 to 0.03% by mass, relative to the total mass of the polyacid and diol containing the alicyclic structure.
[0035] In addition, examples of the above-mentioned polymerization inhibitors include hydroquinone, monomethyl ether hydroquinone, methyl hydroquinone, 2,6-di-tert-butyl-4-methylphenol, trimonomethyl ether hydroquinone, phenothiazine, tert-butylcatechol, etc., which can be used alone or in combination of two or more.
[0036] The amount of the polymerization inhibitor used is preferably 0.001 to 0.3% by mass, more preferably 0.005 to 0.07% by mass, relative to the total mass of the polyacid and diol containing the alicyclic structure.
[0037] Furthermore, the acid value of the aforementioned alicyclic polyester polyol (a1) is preferably 2.0 mg KOH / g or less, more preferably 0 to 1.0 mg KOH / g, and particularly preferably 0 to 0.80 mg KOH / g. The acid value of the aforementioned alicyclic polyester polyol (a1) is a value determined based on JIS K1557-5.
[0038] Furthermore, the hydroxyl value of the aforementioned alicyclic polyester polyol (a1) is preferably 40–220 mg KOH / g, more preferably 50–150 mg KOH / g. The hydroxyl value of the aforementioned alicyclic polyester polyol (a1) can be determined using JIS K0070 as a standard.
[0039] From a synthetic point of view, and from the viewpoint of achieving a balance between adequate open time and moisture-proof properties at low temperatures, the alicyclic polyester polyol (a1) synthesized by the above method preferably has a number average molecular weight of 500 to 2500, more preferably 500 to 1500. It should be noted that the above number average molecular weight is a value obtained by gel permeation chromatography (GPC) using polystyrene as the molecular weight standard.
[0040] In the above-mentioned polyol (A), the content of the above-mentioned alicyclic polyester polyol (a1) is 20% by mass or more, preferably 23% by mass or more, preferably 70% by mass or less, more preferably 50% by mass or less, and even more preferably 48% by mass or less.
[0041] The aforementioned long-chain aliphatic polyester polyol (a2) is an essential component for exerting cohesive force as an adhesive, and refers to a polyester polyol in which the total number of carbon atoms of the alkylene groups contained in the repeating unit is 10 or more.
[0042] From the perspective of foam suppression, the above-mentioned long-chain aliphatic polyester polyol (a2) is preferably represented by the following formula (1).
[0043]
Chemical Formula 1
[0044]
[0045] In equation (1), R 1 and R 2 They are straight-chain alkylene groups with an even number of carbon atoms, and R 1 and R 2 The total number of carbon atoms is 10 or more. n represents an integer from 1 to 40.
[0046] The above R 1 It is a straight-chain alkylene group with an even number of carbon atoms, and can be found in R 1 and R 2 Appropriate selection should be made within the range where the total number of carbon atoms is 10 or more. As R 1 Preferably, it is a straight-chain alkylene group with an even number of carbon atoms (4 or more), and more preferably, it is a straight-chain alkylene group with an even number of carbon atoms in the range of 4 to 10.
[0047] The above R 2 With the above R 1 Independently, it is a straight-chain alkylene group with an even number of carbon atoms, and can be found in R 1 and R 2 The alkylene group is appropriately selected from the range where the total number of carbon atoms is 10 or more, and preferably is an even-numbered linear alkylene group with 4 or more carbon atoms, and more preferably is an even-numbered linear alkylene group with 4 to 12 carbon atoms (preferably 10 to 12).
[0048] R 1 and R 2 The total number of carbon atoms is preferably 10 or more, more preferably 12 or more, for example 30 or less, more preferably 26 or less, and even more preferably 24 or less.
[0049] By using the above R 1 and R 2 The resulting urethane prepolymer, which is a long-chain aliphatic polyester polyol with a number of carbon atoms in the range described above, exhibits improved crystallinity and can be used to obtain a moisture-curing polyurethane hot melt adhesive that can prevent the peeling of the sheet or film at complex-shaped locations on the substrate.
[0050] In formula (1), n represents an integer from 1 to 40, preferably an integer from 9 to 25, and more preferably an integer from 9 to 15. By using a long-chain aliphatic polyester polyol having n in the above range, it is possible to exert a moderate amount of cohesive force as an adhesive.
[0051] The aforementioned long-chain aliphatic polyester polyol (a2) can be manufactured, for example, by a condensation reaction of a straight-chain aliphatic diol with an even number of carbon atoms and a straight-chain aliphatic dicarboxylic acid with an even number of carbon atoms. Examples of the straight-chain aliphatic diols include ethylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, and 1,10-decanediol; 1,6-hexanediol, 1,8-octanediol, and 1,10-decanediol are preferred.
[0052] As the aforementioned straight-chain aliphatic dicarboxylic acid, succinic acid, adipic acid, sebacic acid, dodecyl dicarboxylic acid, etc. can be used, with sebacic acid and 1,12-dodecanedicarboxylic acid being preferred.
[0053] Furthermore, the combination of the linear aliphatic diol and the linear aliphatic dicarboxylic acid used in the manufacture of the above-mentioned long-chain aliphatic polyester polyol (a2) can be expressed in the R of the above formula (1). 1 R 2 The total number of carbon atoms contained therein is preferably selected to be 12 or more, preferably in the range of 12 to 20. Among these, a long-chain aliphatic polyester polyol obtained by reacting 1,6-hexanediol (a linear aliphatic diol) with 1,12-dodecanedicarboxylic acid or sebacic acid (a linear aliphatic dicarboxylic acid) is preferred. Furthermore, the use of a long-chain aliphatic polyester polyol obtained by reacting 1,6-hexanediol (a linear aliphatic diol) with 1,12-dodecanedicarboxylic acid (a linear aliphatic dicarboxylic acid) is more preferable in manufacturing adhesives that possess a practically sufficient level of initial adhesive strength even when used in relatively high-temperature environments.
[0054] The number average molecular weight of the above-mentioned long-chain aliphatic polyester polyol (a2) is preferably 10,000 or less, more preferably 5,000 or less, more preferably 500 or more, more preferably 1,000 or more, and even more preferably 3,000 or more.
[0055] In this invention, the number-average molecular weight can be determined using gel permeation chromatography (GPC) with polystyrene as the standard sample.
[0056] From the perspective of foam suppression, the content of the long-chain aliphatic polyester polyol (a2) in the above-mentioned polyol (A) is 15% by mass or more, preferably 20% by mass or more, more preferably 22% by mass or more, preferably 65% by mass or less, more preferably 40% by mass or less, and even more preferably 35% by mass or less.
[0057] The aforementioned liquid polyester polyol (a3) is an essential component for ensuring adhesion to the PET substrate. It can be a liquid polyester polyol at room temperature (25°C), such as the reaction product of a polyacid containing adipic acid and an aliphatic compound having two or more hydroxyl groups. The aforementioned long-chain aliphatic polyester polyol (a2) differs from the aforementioned liquid polyester polyol (a3).
[0058] Other polyacids besides adipic acid can be used, such as aliphatic polyacids like succinic acid, adipic acid, pimelic acid, octanoic acid, azelaic acid, sebacic acid, decanoic acid, dodecanoic acid, eicosanoic acid, citracic acid, itaconic acid, citracic anhydride, and itaconic anhydride; and alicyclic polyacids like 1,4-cyclohexanedicarboxylic acid. These polyacids can be used alone or in combination of two or more. Among the aforementioned polyacids, the amount of adipic acid used is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more.
[0059] As aliphatic compounds having two or more hydroxyl groups, for example, ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,12-dodecanediol, diethylene glycol, triethylene glycol, tetraethylene glycol, neopentyl glycol, 1,2- Butanediol, 1,3-butanediol, 2-methyl-1,3-propanediol, 2,2-diethyl-1,3-propanediol, 3-methyl-1,5-pentanediol, 2-ethyl-2-butyl-1,3-propanediol, 2-methyl-1,8-octanediol, 2,4-diethyl-1,5-pentanediol, trimethylolethane, trimethylolpropane, pentaerythritol, and other straight-chain or branched aliphatic compounds. These compounds can be used alone or in combination of two or more. Among them, from the perspective of obtaining even better initial adhesive strength and flexibility, it is more preferable to use one or more compounds selected from ethylene glycol, 1,4-butanediol, neopentyl glycol, 1,2-butanediol, 1,3-butanediol, 2-methyl-1,3-propanediol, 3-methyl-1,5-pentanediol, 2-ethyl-2-butyl-1,3-propanediol, and 2,4-diethyl-1,5-pentanediol.
[0060] Regarding the number-average molecular weight of the aforementioned liquid polyester polyol (a3), from the viewpoint of obtaining even better initial adhesive strength and flexibility, it is preferably 300 or more, more preferably 600 or more, even more preferably 1,000 or more, more preferably 10,000 or less, and more preferably 9,000 or less.
[0061] The glass transition temperature of the above-mentioned liquid polyester polyol (a3) is preferably below 20°C, more preferably below 10°C, and even more preferably below 5°C. For example, it can also be above -100°C or above -50°C.
[0062] The aforementioned glass transition temperature can be determined by DSC based on JIS K 7121-1987. Specifically, the sample is placed in a differential scanning calorimeter, heated to (Tg+50℃) at a rate of 10℃ / min, held for 3 minutes, and then rapidly cooled. The glass transition temperature (Tmg) at the midpoint of the obtained differential calorimeter curve is set as the glass transition temperature.
[0063] In the above-mentioned polyol (A), the content of the above-mentioned liquid polyester polyol (a3) is 15% by mass or more, more preferably 20% by mass or more, even more preferably 25% by mass or more, preferably 65% by mass or less, more preferably 55% by mass or less, and even more preferably 50% by mass or less.
[0064] In the above-mentioned polyol (A), the total content of the above-mentioned alicyclic polyester polyol (a1), long-chain aliphatic polyester polyol (a2), and liquid polyester polyol (a3) is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 90% by mass or more, and preferably 100% by mass.
[0065] In addition to the alicyclic polyester polyol (a1), the long-chain aliphatic polyester polyol (a2), and the liquid polyester polyol (a3) mentioned above, other polyols may be used as needed as the polyol (A).
[0066] Other polyols mentioned above can be polyester polyols, polycarbonate polyols, polyacrylic acid polyols, butadiene polyols, hydrogenated polybutadiene polyols, etc., other than those mentioned in (a1), (a2), and (a3). These polyols can be used alone or in combination of two or more.
[0067] As the aforementioned polyisocyanate (B), for example, aromatic polyisocyanates such as polymethylene polyphenyl polyisocyanate, diphenylmethane diisocyanate, carbodiimide-modified diphenylmethane diisocyanate, phenylene diisocyanate, toluene diisocyanate, and naphthalene diisocyanate can be used; aliphatic or alicyclic polyisocyanates such as hexamethylene diisocyanate, lysine diisocyanate, cyclohexane diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, phenylenediamine diisocyanate, and tetramethylphenylenediamine diisocyanate can be used. Among these, aromatic polyisocyanates are preferred from the perspective of obtaining further superior reactivity and final adhesive strength, and diphenylmethane diisocyanate is more preferred.
[0068] Furthermore, regarding the amount of polyisocyanate (B) used, from the perspective of obtaining even better adhesive strength, it is preferably in the range of 5 to 60% by mass in the raw materials of polyurethane resin, and more preferably in the range of 15 to 50% by mass.
[0069] The polyurethane resin described above is a product obtained by reacting the polyol (A) with the polyisocyanate (B) described above, and has isocyanate groups at the polymer ends and within the molecule that can react with moisture present in the air, the shell coated with the urethane prepolymer, or the adhesive to form a cross-linked structure.
[0070] As a method for manufacturing the above-mentioned polyurethane resin, it can be manufactured, for example, by adding the above-mentioned polyol (A) dropwise to a reaction vessel in which the above-mentioned polyisocyanate (B) is added, heating it, and reacting it under conditions where the isocyanate groups of the above-mentioned polyisocyanate (B) are in excess relative to the hydroxyl groups of the above-mentioned polyol (A).
[0071] The amount of urethane bonds in the polyurethane resin is preferably in the range of 0.5 to 3 mol / kg, more preferably in the range of 0.9 to 2.7 mol / kg, and even more preferably in the range of 1.1 to 2.4 mol / kg, from the viewpoint of obtaining even better initial bond strength, flexibility and low viscosity.
[0072] The equivalent ratio ([isocyanate group / hydroxyl group]) of the isocyanate group in the polyisocyanate (B) to the hydroxyl group in the polyol (A) during the manufacture of the polyurethane resin is preferably in the range of 1.1 to 1.5, more preferably in the range of 1.15 to 1.45, from the viewpoint of obtaining further superior initial adhesive strength, flexibility and low viscosity.
[0073] The isocyanate group content (hereinafter referred to as "NCO%)" of the aforementioned polyurethane resin is preferably in the range of 1 to 4% by mass, and more preferably in the range of 1.2 to 3.5% by mass, from the viewpoint of obtaining further superior initial bond strength, flexibility, and low viscosity. It should be noted that the NCO% of the aforementioned polyurethane resin represents a value determined by potentiometric titration based on JIS K 1603-1:2007.
[0074] In the above-mentioned moisture-curing polyurethane hot melt resin composition, the content of the polyurethane resin is preferably 40% by mass or more, more preferably 60% by mass or more, even more preferably 80% by mass or more, and the upper limit is 100% by mass.
[0075] In addition to the polyurethane resin described above, the moisture-curing polyurethane hot melt resin composition of the present invention may also contain other additives as needed.
[0076] Other additives mentioned above may include antioxidants, thickeners, plasticizers, stabilizers, fillers, dyes, pigments, optical brighteners, silane coupling agents, waxes, etc. These additives may be used alone or in combination of two or more.
[0077] As a method for obtaining the cured film of the above-mentioned moisture-curing polyurethane hot melt resin composition, for example, a method is to melt the above-mentioned moisture-curing polyurethane hot melt resin composition at 50 to 130°C, apply it to a substrate, and then allow it to be moisture-cured.
[0078] Examples of suitable substrates include wood-based substrates such as plywood, MDF (medium-density fiberboard), and particleboard; metal-based substrates such as aluminum and iron; sheet-like substrates made from resins such as polyester, polyamide, polystyrene, polycarbonate, vinyl chloride, ethylene-vinyl acetate copolymer, polyvinyl alcohol, polyethylene, and polypropylene; calcium silicate boards; paper; metal foil; veneer; fiber-based substrates such as non-woven fabrics and woven fabrics; synthetic leather; paper; rubber-based substrates; and glass-based substrates. The thickness of these substrates can be determined according to their intended use, and may range from 1 to 500 mm.
[0079] As a method for coating the aforementioned moisture-curing urethane hot melt resin composition onto the aforementioned substrate, examples include the following methods: using a coating machine such as a roller coater, sprayer, T-die coater, doctor blade coater, or comma coater; or using precision methods such as a dispenser, jetting, inkjet printing, screen printing, or offset printing to coat the moisture-curing urethane hot melt resin composition, which has been melted at 70–140°C, onto the substrate.
[0080] The thickness of the cured layer of the above-mentioned moisture-curing urethane hot melt composition is appropriately determined according to the application, for example, in the range of 0.001 to 3 cm.
[0081] After the above coating is applied, it can be aged for 0.5 to 3 days at a temperature of 20 to 80°C and a relative humidity of 50 to 90% to obtain the final bonding strength.
[0082] The moisture-curing polyurethane hot melt resin composition of the present invention ensures transparency and inhibits foaming even after moisture curing, thereby exhibiting adhesion to PET substrates. Therefore, the moisture-curing polyurethane hot melt resin composition of the present invention can be suitable for use in building material panels, decorative panels, automotive interior materials, etc.
[0083]
Example
[0084] The present invention will be described in more detail below with reference to specific embodiments, but the present invention is not limited to the following embodiments at all. Of course, it can also be implemented by appropriate modifications within the scope of the above and below spirit, and these are all included in the technical scope of the present invention.
[0085] [Example 1]
[0086] Add 24 parts by weight of aliphatic polyester polyol (a substance obtained by reacting diethylene glycol, neopentyl glycol, 1,6-hexanediol, and adipic acid; number average molecular weight: less than 2,000; hereinafter referred to as "DEG / NPG / HG / AA2000"), 38 parts by weight of alicyclic polyester polyol (a product of the reaction of neopentyl glycol and hexahydrophthalic anhydride; number average molecular weight: 2,000; hereinafter referred to as "NPG / HHPA2000"), and 20 parts by weight of crystalline polyester polyol (a product of the reaction of 1,6-hexanediol and dodecanoic acid; number average molecular weight: 3,500; hereinafter referred to as "HG / DDA3500") to a four-necked flask equipped with a stirrer and thermometer. Dehydrate under reduced pressure at 100°C until the water content in the flask reaches 0.05% by weight. After cooling the flask to 90°C, 18 parts by weight of 4,4'-diphenylmethane diisocyanate (hereinafter referred to as "MDI") molten at 70°C were added. The mixture was then reacted at 110°C for about 1 hour under a nitrogen atmosphere until the NCO% became constant, thereby obtaining a moisture-curing polyurethane hot melt resin composition.
[0087] [Example 2, Comparative Examples 1-3]
[0088] Except for changing the amount of polyol and polyisocyanate used as shown in Table 1, the same procedure as in Example 1 was followed to obtain a moisture-curing polyurethane hot melt resin composition.
[0089] The resulting moisture-curing polyurethane hot melt resin composition was evaluated as follows.
[0090] [Methods for evaluating transparency]
[0091] After melting the moisture-curing polyurethane hot melt adhesive obtained in the examples and comparative examples at 120°C for 1 hour, a 0.10 mm thick film was formed on the inside of the release paper using a roller coater. It was then cured at 23°C and 50% humidity for at least 4 days to allow the moisture curing reaction to complete. The haze value of the cured RHM film was measured using a haze meter and evaluated as follows.
[0092] “○”: Haze value is less than 20.
[0093] "×": Haze value is 20 or higher.
[0094] [Evaluation methods for the appearance of foamed products]
[0095] After melting the moisture-curing polyurethane hot melt adhesive obtained in the examples and comparative examples at 120°C for 1 hour, a 0.10 mm thick film was formed on the inside of the release paper using a roller coater. It was then cured at 40°C and 50% humidity for at least 12 hours to allow the moisture curing reaction to proceed as quickly as possible. The cured RHM film was visually inspected and evaluated as follows.
[0096] “○”: The bubble cannot be identified by visual inspection.
[0097] "×": The bubble can be identified visually.
[0098] [Evaluation Methods for PET Adhesion]
[0099] The moisture-curing polyurethane hot melt adhesive obtained in the examples and comparative examples was melted at 120°C for 1 hour and then applied to a PET sheet at a thickness of 0.05 mm using a laminator. It was then bonded to a melamine decorative panel using a pressure roller. After being placed in an environment of 23°C and 50% humidity for 4 days, a 180° peel test was performed with a width of 2.5 cm. The peel strength was measured and evaluated as follows.
[0100] “○”: Peel strength is above 40 N / inch.
[0101] "×": Peel strength less than 40 N / inch.
[0102] The evaluation results are shown in Table 1.
[0103] Table 1
[0104]
[0105] Examples 1 and 2 are embodiments of the present invention. They maintain transparency and suppress foaming after moisture curing, and also have good adhesion to the PET substrate.
[0106] Comparative Example 1 is an example with a low content of long-chain aliphatic polyester polyol, and foaming during moisture curing was not sufficiently suppressed.
[0107] Comparative Example 2 is an example with a low content of liquid polyester polyol, resulting in insufficient adhesion to the PET substrate.
[0108] Comparative Example 3 is an example with a low content of alicyclic polyester polyol, and its transparency is insufficient.
[0109] Industrial availability
[0110] The moisture-curing polyurethane hot melt resin composition of the present invention ensures transparency and inhibits foaming even after moisture curing, thereby exhibiting adhesion to PET substrates. Therefore, the moisture-curing polyurethane hot melt resin composition of the present invention can be suitable for use in building material panels, decorative panels, automotive interior materials, etc.
Claims
1. A moisture-curing polyurethane hot melt resin composition comprising a polyurethane resin having isocyanate groups, The polyurethane resin is a reaction product of polyol A and polyisocyanate B. The polyol A comprises an alicyclic polyester polyol a1, a long-chain aliphatic polyester polyol a2 in which the total number of carbon atoms of the alkylene groups contained in the repeating units is 10 or more, and a liquid polyester polyol a3. The alicyclic polyester polyol a1 contains more than 20% by mass in polyol A. The long-chain aliphatic polyester polyol a2 contains more than 15% by mass in polyol A. The liquid polyester polyol a3 contains more than 15% by mass in polyol A.
2. The moisture-curing polyurethane hot-melt resin composition according to claim 1, wherein the haze value measured by the following method is less than 20, [Methods for determining haze value] The moisture-curing polyurethane hot melt resin composition was melted at 120°C for 1 hour and coated onto the release layer to achieve a thickness of 0.1 mm. The resulting coating layer was kept at 23°C and 50% humidity for 96 hours to obtain a cured product. The haze value of the cured product was measured according to JIS K 7136.
3. A cured product, which is a cured product of the moisture-curing polyurethane hot melt resin composition according to claim 1 or 2.
4. A laminate having the cured material of claim 3.
Citation Information
Patent Citations
Hot melt adhesive composition excellent in transparency
JP2015108113A
Hot-melt adhesive for laminate and laminated film laminate using the same
JP2018154694A
Hot-melt adhesive excellent in transparency and chemical resistance
JP2019127581A
Hot melt adhesive for laminate, and laminate film laminate using the same
JP2020002283A
Reactive hot melt adhesive
JP1994093244A